Suppression of Radiation-Induced Testicular Germ Cell Apoptosis by 2,5-Hexanedione Pretreatment. I. Histopathological Analysis Reveals Stage Dependence of Attenuated Apoptosis - Yamasaki, Hideki (Oxford University Press, 2010)
In the testis, developing germ cells are dependent on supportive physical and paracrine interactions with Sertoli cells. The intimate nature of this relationship is demonstrated by the fact that a toxic insult compromising the stability of Sertoli cells will have deleterious effects on the associated germ cells. 2,5-Hexanedione (HD) and x-radiation (x-ray) are testicular toxicants, each with a unique cellular target. HD exposure disrupts microtubule function in Sertoli cells, and x-ray exposure causes double-strand breaks in the DNA of germ cells. Despite their differing modes of action, exposure to either toxicant has the similar ultimate effect of increased germ cell apoptosis. In this study, adult male F344 rats were exposed to 1% HD in the drinking water for 18 days with or without coexposure to 2 or 5 Gy x-ray 12 h prior to necropsy. Incidence of retained spermatid heads was increased in the HD and coexposure groups. Germ cell apoptosis was significantly increased in the x-ray and coexposure groups. There was a striking stage-dependent attenuation of apoptosis with coexposure compared with x-ray alone. Detailed histopathological analysis revealed a significant suppression of x-ray–induced germ cell apoptosis by HD pretreatment in stages I–VI of the seminiferous cycle, most noticeably at stages II/III. We hypothesize either that subacute HD pretreatment compromises the ability of the Sertoli cells to eliminate x-ray–damaged germ cells or that germ cells are more resistant to x-ray–induced damage, having adapted to a less supportive environment.